Understanding Ethnic Groups as Socio-Cultural Constructions and Social Order: A Systematic Literature Study - Marzuti Isra; Wulan Cintami Sri Rezeki Manurung; Rahmayani Salsabila Siregar; Geonesimus Karo-Karo; R. Bima Prayoga; Habib Ghulam Azhari Barus (Jurnal Multidisiplin Sahombu, 2025)
This systematic literature review examines ethnic groups as socio-cultural constructions and their role in social order. Through an analysis of 25 key publications (2000–2023), the study reveals that ethnic groups are not static biological entities but dynamic outcomes of negotiations between individual agency and social structures via identity practices, policies, and power relations. Ethnicity plays an ambivalent role: as a cohesive force based on Gemeinschaft (Francis, 1947) and as a trigger for stratification when politicized (Brass et al., 2000). The theoretical implications emphasize the need to update ethnicity frameworks based on local contexts and integrate cognitive psychology (Gil-White, 2001), while practical implications advocate for integrating ethnic perspectives into inclusive health policies (Aldridge et al., 2023) and multicultural political systems (Shapiro & Kymlicka, 2020). A key limitation is the dominance of Western literature. Future research should explore ethnicity in the digital society era and comparative studies of ethnic construction in Asia versus the West.